The Influence of Work Motivation on the Performance of Clinical Nurses at the Regional Public Hospital (RPH) Haji Makassar - Fitri, A. Ulfiana; Ariani, Ni Wayan; Fitriani, Dian Ayu (SIGn Journal of Public Health, 2025)
In the dynamic post-pandemic healthcare landscape, RPH Haji Makassar faces the dual challenge of transitioning to electronic medical records and optimizing operational efficiency, as reflected by a Bed Occupancy Rate (BOR) that has yet to meet national standards. Although nurses play a central role as frontline providers, inefficiencies in care management are frequently observed, indicating the need for an in-depth evaluation of the psychological factors underlying clinical performance. This study aims to comprehensively analyze the effects of intrinsic and extrinsic work motivation on the performance of staff nurses in the inpatient wards of RPH Haji Makassar in 2025. This study employed a quantitative, cross-sectional design and involved 144 staff nurses as respondents, using a total sampling (census) technique. Primary data were collected using a validated, structured questionnaire, and analysis was conducted using a simple linear regression to test the hypothesis. Empirical findings revealed that the majority of nurses possessed a very high level of work motivation (93.75%), consistently accompanied by a high rate of performance achievement (94.44%). Statistical analysis confirmed a positive and significant effect of work motivation on nurse performance (p-value = 0.001; p < 0.05), with the regression coefficient indicating that strengthening motivation directly contributes to improved service quality. The high motivation of nurses proved to be a primary pillar of service resilience amidst work pressure and the adaptation to new technology; however, a gap remains between excellent individual performance and macro-level organizational efficiency. Work motivation is a vital predictor of nurses’ clinical performance. This study recommends managerial strategies that focus not only on financial incentives but also on strengthening psychosocial support and creating an adaptive work environment to align individual performance with the hospital’s strategic goals.